Le Messager du Brésil (RJ, 1878-1884): trajectory in three movements - De Luca, Tania Regina [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2022)
This article analyzes the trajectory of the newspaper Le Messager du Brésil, written in French and printed in Rio de Janeiro. From the analysis of the available collections emerge three distinct moments that point to the newspaper’s increasing involvement in Brazilian political debates, scenario in which Le Messager was far from a passive observer. The example invites us to review the image normally associated with the press published in foreign language in the literature regarding the Brazilian press, which, more often than not, see them as circumscribed to specific groups, undermining their political action.
Le Messager du Brésil (RJ, 1878-1884): Trajetória em três movimentos
Keywords: Crisis of slaveryy; Francophone press; Le Messager du Brésil; Émile Deleau